Efficacy, safety, and pharmacokinetics of inhaled treprostinil in Japanese patients with pulmonary arterial hypertension. (8th February 2023) - Kuwana, Masataka; Abe, Kohtaro; Kinoshita, Hideyuki; Matsubara, Hiromi; Minatsuki, Shun; Murohara, Toyoaki; Sakao, Seiichiro; Shirai, Yuichiro; Tahara, Nobuhiro; Tsujino, Ichizo; Takahashi, Kenta; Kanda, Shingo; et al.
Abstract: Treprostinil is a chemically stable analog of prostacyclin, and inhaled treprostinil was developed to deliver the effects directly to the pulmonary vasculature while minimizing systemic side effects. The objective of the study was to evaluate the efficacy on hemodynamics and exercise capacity, safety, and pharmacokinetics (PK) of inhaled treprostinil in Japanese patients with pulmonary arterial hypertension (PAH). Inhaled treprostinil was administered at three breaths (18 μg)/session four times daily, and the dose was gradually increased to a maximum of nine breaths (54 μg)/session. Endpoints included change in pulmonary vascular resistance index (PVRI) as primary, other efficacy parameters, safety, and PK. Seventeen PAH patients, the majority of whom (76.5%) had been receiving both an endothelin receptor antagonist (ERA) and a phosphodiesterase type‐5 (PDE5) inhibitor/soluble guanylate cyclase (sGC) stimulator, received inhaled treprostinil. At Week 12, PVRI statistically decreased by −39.4 ± 25.5% (95% confidence interval: −52.6 to −26.3). The most frequently reported adverse events related to treprostinil were headache, cough, throat irritation, and hot flush. Regarding PK, there were no notable differences in the geometric mean C max and AUClast between Japanese and non‐Japanese patients. Treatment with inhaled treprostinil using the dosing regimen approved in the United States resulted in significant improvement in hemodynamics, exercise capacity, and symptoms with a favorable tolerability and safety profile in Japanese patients. Inhaled treprostinil could be a valuable therapeutic option for Japanese patients with PAH, including those receiving a combination therapy with an ERA and a PDE5 inhibitor/sGC stimulator. Trial registration: JAPIC Clinical Trials Information [JapicCTI‐194651].